Planning a Radiotherapy Department. Issue 2 (February 2017) - van der Merwe, D.
Abstract: The master planning of new radiotherapy facilities requires the input and engagement of a range of highly specialised professionals, both in the construction and health sector. Although radiation protection and safety aspects of radiotherapy services are universal, low and middle income countries are often presented with unique challenges that also need to be considered, e.g. competing needs within the health sector, lack of financial and human resources, environmental factors like poor provision of transport or electrical power, inadequate regulatory infrastructure, etc. Efforts to establish, upgrade or expand radiotherapy services should therefore not only focus on the technology that is appropriate and sustainable, but also be mindful of the need for quality, safety and optimal utilisation of technology. The workflow in a radiotherapy department can be facilitated by strategic placement of the main functional areas into the concept design.